The effect of adolescent reproductive health education on premarital sexual behavior - Murdiningsih Murdiningsih; Rohaya Rohaya; St Hindun; Ocktariyana Ocktariyana (International Journal of Public Health Science (IJPHS), 2020)
A lack of communication, support, and information from parents on sexual issues are involved an inability to prevent or intervene in the sexual activity of adolescents. This study aimed to determine the effect of adolescent reproductive health education on premarital sexual behavior in Palembang, Indonesia. This study was an experimental design with pre and post-intervention. The 192 students were obtained based on the criteria of samples required. The result of bivariate analysis between the Chi-Square confounding variable and premarital sexual behavior after the intervention shows that there is a significant relationship between knowledge about sex, reproductive health, and attitudes with premarital sexual behavior. There is a significant relationship between control behavior and sexual behavior after performing the intervention (p= 0.00). The result of multivariate shows that there is a dominant variable that is the variable of knowledge about reproductive health (p= 0.00). This study suggested that information about adolescent reproductive health should be included in the curriculum, especially in Biology class.